IN VITRO EVALUATION OF ANTIBIOTIC CONJUGATED BIOGENIC GOLD NANOPARTICLES BY NEOSARTORYA UDAGAWAE - V. JHANSI LAKSHMI,; K.P. KANNAN, (International Journal of Pharma and Bio Sciences, 2016)
Gold nanoparticles (AuNPs) were synthesized in a novel single step method by fungus Neosartorya udagawae and characterized by UV-Vis spectrophotometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Gold nanoparticles have the absorption maxima at 536 nm and size ranges from 50 to 53nm. Gold nanoparticles were conjugated with antibiotics Amoxicillin, Streptomycin and Gentamycin. Conjugation was confirmed by UV–Vis, SEM and TEM. Conjugation process enhanced the antimicrobial efficacy of the antibiotics over free AuNPs and standard drugs against E. coli. The antibacterial effect was confirmed by antibody diffusion method and AuNPs conjugated with antibiotic Streptomycin are highly effective against E. coli than Amoxicillin and Gentamycin conjugates due to greater stability and higher anti-microbial activity.